Previsão de anóxia em reservatórios tropicais semiáridos nos períodos chuvoso e seco - Carneiro, Brenda Lara Duarte Souza (2022)
The level of dissolved oxygen (DO) in the hypolimnion of lakes and reservoirs can lead to anoxic conditions, which favor the release of phosphorus by the bottom sediment in the column of water. However, to estimate the nutrient release from the sediment it is extremely important to quantify the duration of anoxia. In low latitude regions, the waters near to sediments are warmer than in temperate regions and eutrophication is generally more severe, potentially accelerating oxygen depletion, extending the anoxic period and causing the thickening of the anoxic layer, factors that can lead to mortality of organisms, notably fish, present in the aquatic biota. Considering that the available equations to quantify the duration of anoxia were developed for lakes temperate, there was a need to effectively quantify this period in lakes and reservoirs located in other climatic regions, such as the semiarid. In this study, it was analyzed the dynamics of thermal stratification, as a function of the Stability coefficient Relative Water Column (RWCS), which was correlated with the behavior of the OD for nineteen semi-arid tropical reservoirs, located in the State of Ceará. The values of RWCS were higher during the rainy season, when the duration of anoxia was longer. prolonged and the hypolimnion was thicker in relation to the total depth of the Water. Then, two new equations to quantify the duration of anoxia, based on the equation original developed for temperate climates, were adapted for the rainy and dry seasons of the tropical semiarid region. The results showed that the proposed equations presented higher performance compared to the original equation, which has a tendency to underestimate the anoxia in the reservoirs. This work provides a simple and fine-tuned tool locally to better quantify anoxia events and support quality modeling of water and internal phosphorus load for semi-arid tropical reservoirs